(untitled) (LACCEI, 2024)
In the present investigation, the purpose is to determine the compressive strength of a 210 kg/cm2 concrete exposed to sulfates, for which 5%, 10% and 15% of recycled majolica that passes through mesh No. 4, of which a total of 108 concrete witnesses were considered, separated into 27 for each design variation, having an experimental type methodology, application level and quantitative design. The mix design by the ACI method, considering as a premise if the recycled majolica not only contributes to the resistance to compression, but also against pathogens, so it was decided to use magnesium sulfate as an active agent for the pathology. Obtaining as a result after 28 days: standard concrete is 223.77 kg/cm2, exposed concrete 199.77 kg/cm2, with 5% majolica 184 kg/cm2, 5% exposed majolica is 165.98 kg/cm2, 10% majolica of 191.03 kg/cm2, 10% exposed majolica is 170.23 kg/cm2, 15% majolica with 208.20 kg/cm2 and 15% exposed majolica 183.07 kg/cm2. The concrete of 210 kg/cm2 with the addition of 15% recycled majolica reaches 208 kg/cm2 without being exposed to curing with magnesium sulfate and with exposure to magnesium sulfate it reaches 183.07 kg/cm2, concluding that the addition of recycled majolica contributes to compressive strength as well as exposure to pathogens.